SELF REGULATED LEARNING OF VOCATIONAL STUDENTS IN MATHEMATICS LEARNING DURING COVID-19 PANDEMIC - Lestari, Winda; Maimunah, Maimunah; Roza, Yenita (Jurnal Pendidikan Matematika dan IPA, 2022)
The Covid-19 pandemic that is currently sweeping the world, including Indonesia, made the government make the decision to implement PSBB (large-scale social restrictions) by asking people to stay at home, including the learning process at school. The learning process carried out online or online indirectly makes students adapt to the new learning process. Students are required to be able to do self-regulation in learning (self regulated learning). Self regulated learning is important for students, especially when learning is carried out online. This study aims to obtain a picture of self-regulated learning of class XI SMK students during the Covid-19 pandemic. This research is a quantitative-descriptive study using a survey method. The instrument used was a self-regulated learning questionnaire which had 23 statement items. Data collection was carried out using an online questionnaire on google form which was given to students of class XI Fashion Design Vocational Schools. The results of the SRL research for students of class XI Fashion Design at SMK Negeri 3 Pekanbaru during the pandemic were 17% students with high SRL, 53% students with moderate SRL and 30% students with low SRL. tudent's SRL is low on indicators of evaluating learning processes and outcomes as well as self-efficacy (self-concept), this is influenced by individual, behavioral and environmental factors.